Architecture of landed house property business strategy (Case study of PT KGC) - Sanjaya, Irsyad; Ma'arif, Mohamad Syamsul; Hannan, Sufrin (Indonesian Journal of Multidisciplinary Science, 2023)
Among the property development companies operating in Cibubur, PT KGC and PT SM are the same entity from the one holding company. PT SM demonstrates positive performance for last 4 years while PT KGC showing fluctuation performance over the past four years., therefore, PT KGC required to formulating a new strategy to compete on the landed house property business. The objective of this research is to identify the issues in the landed house business competition, formulate alternative strategies, and determine priority strategies for PT KGC to address the competition in the landed house business. The research methodology employs IFE (Internal Factor Evaluation), EFE (External Factor Evaluation), SWOT (Strengths, Weaknesses, Opportunities, Threats), and QSPM (Quantitative Strategic Planning Matrix). The research shows that inadequate implementation of existing strategies has led to unstable company performance over the past four years, causing decreased revenue, vendor payments, and delays in housing construction. The Quantitative Strategic Planning Matrix recommends strategies like market penetration, product development, and market development to improve the company's position in the profitable land-based housing industry.